ANALYSIS OF BOERJA GOAT ANIMAL BUSINESS PROFITABILITY (Case Study at CV. Agriranch Kelurahan Tawangargo, Kecamatan Karangploso, Kabupatan Malang) - Sin, Maria Yohaneta; Sumarno, Sumarno; Santoso, Erik Priyo; Murti, Ariani Trisna (Universitas Tribhuwana Tunggadewi, 2019)
The purpose of the research is to know the amount of income and the value of profitability of the goat livestock business. The research was conducted at